Implementing an Occupational Therapy Low Vision Rehabilitation Program in Singapore. (September 2019) - Boey, Debbie Shuying; Warren, Mary
Introduction: This article describes the development, implementation, and evaluation of an occupational therapy (OT) low vision rehabilitation program established in a large hospital in Singapore in 2013. Methods: A logic model was used to develop a blueprint to guide program development and evaluation of the program. The targeted short-term outcomes for the first 2 years are to demonstrate program growth through an increase in referrals and meeting of clients' needs through expressed client satisfaction and improvement in performance of daily activities. The long-term outcomes are to expand the program's referral base and contribute to education and research in low vision rehabilitation. The steps of the logic model are described along with program evaluation results from the first 2 years of implementation. Results: The short-term outcome for program growth was met with the increase of referrals in the first 2 years. Program evaluation, however, revealed that there was limited support from some referral sources and underutilization of OT services, which need to be addressed to ensure sustainability of the program. It was difficult to establish whether the short-term outcomes for meeting clients' needs were met due to limited outcome measures completed. Discussion: The logic model guided the steps of developing and evaluating an outpatient low vision rehabilitation program in a hospital in Singapore to determine whether the targeted outcomes were met for the first 2 years of the program. Use of this process enabled the program providers to identify weaknesses in the program and institute steps to move the program toward achievement of its long-term goals. Implications for practitioners: This blueprint can be used to guide occupational therapists developing medically based low vision rehabilitation programs for older adults.